2020
DOI: 10.1016/j.pharmthera.2020.107697
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the research on the targets of anti-malaria actions of artemisinin

Abstract: Malaria has been a global epidemic health threat since ancient times. It still claims roughly half a million lives every year in this century. Artemisinin and its derivatives, are frontline antimalarial drugs known for their efficacy and low toxicity. After decades of wide use, artemisinins remain our bulwark against malaria. Here, we review decades of efforts that aim to understand the mechanism of action (MOA) of artemisinins, which help explain the specificity and potency of this anti-malarial drug. We summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
46
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(46 citation statements)
references
References 110 publications
0
46
0
Order By: Relevance
“…Furthermore, many research groups have used radio-labeled or fluorescent-labeled probes to identify the targets of a range of bioactive NPs, such as the flavonoid 7-O-cinnamoyl paclitaxel ( Gunesch et al, 2020 ) , xanthohumol from hops ( Brodziak-Jarosz et al, 2016 ) , and artemisinin ( Yang J. et al, 2020 ) . Cephalosporin I, which was recently synthesized by Amatuni’s group using facile chemoenzymatic synthesis, exhibited selectivity for proteasome subunits β2 and β5 after the introduction of fluorescent labels.…”
Section: Chemical Probe Approachmentioning
confidence: 99%
“…Furthermore, many research groups have used radio-labeled or fluorescent-labeled probes to identify the targets of a range of bioactive NPs, such as the flavonoid 7-O-cinnamoyl paclitaxel ( Gunesch et al, 2020 ) , xanthohumol from hops ( Brodziak-Jarosz et al, 2016 ) , and artemisinin ( Yang J. et al, 2020 ) . Cephalosporin I, which was recently synthesized by Amatuni’s group using facile chemoenzymatic synthesis, exhibited selectivity for proteasome subunits β2 and β5 after the introduction of fluorescent labels.…”
Section: Chemical Probe Approachmentioning
confidence: 99%
“…As shown in recent years, many polycyclic endoperoxides, both natural and synthetic, have antimalarial effects [ 21 , 22 ]. It is known that malaria or “swamp fever” refers to a group of transmissible infectious diseases transmitted to humans by bites of female mosquitoes belonging to the genus Anopheles, caused by parasitic protists of the genus Plasmodium, mainly P. falciparum [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Through extensive research on artemisinin, researchers revealed that its primary anti-malarial activity is due to special internal structures called endoperoxide linkages (peroxide bridges) [ 33 ]. When the malaria parasites invade the human body, they digest a large amount of hemoglobin in host erythrocytes to obtain the nutrients necessary for growth and maturation.…”
Section: Introductionmentioning
confidence: 99%